Development of novel multiplex microsatellite polymerase chain reactions to enable high-throughput population genetic studies of Schistosoma haematobium. Issue 1 (December 2015) - Webster, B.; Rabone, M.; Pennance, T.; Emery, A.; Allan, F.; Gouvras, A.; Knopp, S.; Garba, A.; Hamidou, A.; Mohammed, K.; Ame, S.; Rollinson, D.; et al.
Abstract Background Human urogenital schistosomiasis caused bySchistosoma haematobium is widely distributed across Africa and is increasingly targeted for control and regional elimination. The development of new high-throughput, cost-effective molecular tools and approaches are needed to monitor and evaluate the impact of control programs on the parasite populations. Microsatellite loci are genetic markers that can be used to investigate how parasite populations change over time and in relation to external influences such as control interventions. Findings Here, 18 existingS. haematobium microsatellite loci were optimised to enable simultaneous amplification across two novel multiplex microsatellite PCR's, each containing nine loci. Methods were developed for the cost effective and rapid processing and microsatellite analysis ofS. haematobium larval stages stored on Whatman-FTA cards and proved robust on miracidia and cercariae collected from Zanzibar and Niger. Conclusion The development of these novel and robust multiplex microsatellite assays, in combination with an improved protocol to elute gDNA from Whatman-FTA fixed schistosome larval stages, enables the high-throughput population genetic analysis ofS. haematobium . The molecular resources and protocols described here advance the way researchers can perform multi locus-based population genetic analyses ofS. haematobium as part of the evaluation and monitoring of schistosomiasis control programmes.